Legal and Policy Regulations of Performance Requirements for Foreign Investors in Bangladesh - Hossain, Mohammad Belayet; Yeon, Asmah Laili Bt; Aziz, Ahmad Shamsul Bin Abd. (Society & Sustainability, 2020)
The multinational enterprises (MNEs) have a common intention to maximizing their capital investment to gain more profit. In doing so, sometimes they behave irresponsibly towards the host countries, even do not hesitate to bypass the laws of the country. In relation to performance requirements for foreign investors, the host country like Bangladesh may have specific laws or policies; but due to the desire to attract more FDI and pressure from the MNEs, the government may be reluctant to impose various requirements or refrain from enforcing them. This paper will discuss the negative impact of FDI in Bangladesh due to lack of performance requirement provisions> It will also highlight the significance of enacting such provisions into the FDI laws. This paper will address one major question: why the foreign investors should be required to fulfill performance requirements during their entry in Bangladesh? In this study, six respondents were interviewed for expert opinions. The findings of this study show that the existing laws and policies of Bangladesh significantly lack performance requirement provisions. In this relation, recommendations have been provided for consideration by the government.